Rediscovery of Traditional Plant Medicine: An Underestimated Anticancer Drug of Chelerythrine - Chen, Nianzhi; Qi, Yulin; Ma, Xiao; Xiao, Xiaolin; Liu, Qingsong; Xia, Ting; Xiang, Juyi; Zeng, Jinhao; Tang, Jianyuan (Frontiers in Pharmacology, 2022)
Many studies were identified the extensive and significant anticancer activity of Chelerythrine (CHE), which is the mainly natural active compound in four traditional botanical drugs and can be a promise treatment in many kinds of solid tumours, so this review aims to summarize the anticancer abilities and the antitumour mechanism of CHE. The literature searches revolving around this natural compound CHE have been carried out on PubMed, Web of Science, Science Direct, and Medline databases. Increasing evidence indicates that CHE, as a benzophenanthridine alkaloid, exhibits excellent anticancer activity. CHE can intervene in tumour progression and inhibit tumour growth in many ways, such as induction of cancer cell apoptosis, inhibition of cell cycle arrest, inhibition of tumour invasion and metastasis, autophagy-mediated cell death, interaction with DNA with good selectivity for G-quadruplex, reactive oxygen species (ROS), mitogen activated protein kinase (MAPK), and PKC, and many studies have investigated the role of CHE against different types of cancer. Drug discovery programs have identified CHE as the main antitumour drug candidate. The current complex data suggest the potential value with clinical application and future direction of CHE as a therapeutic drug in cancer. Furthermore, this review also highlights the limitations and the current problems. Although the molecular targets of CHE are not yet clearly delineated, extensive research in this area continues to provide new data that are clinically exploitable, while addressing the present need for further studies such as toxicological studies, combination medication, and development of novel chemical methods or biomaterials to increase the effects of CHE or the development of its derivatives and analogues, contributes to this underestimated anticancer drug being effectively translated into clinical practice. We believe that this review can provide help for the clinical application of a new anticancer drug in the future.